Completion of Waste Heat Recovery and CO2 Conversion Simultaneously Based on the Flue Gas Chemical Recuperative Cycle: A Review - Mengze He; Ping Zhou; Xiqiang Zhao; Tao Wang (Energies)
Energy shortage and greenhouse gas emission have become bottlenecks in current society development. Improving the efficiency of energy conversion and utilization systems through waste heat recovery and reduction of greenhouse gas through CO2 capture/conversion are important solutions. Both can be achieved simultaneously by utilizing high-temperature flue gas or CO2 in flue gas for organic matter gasification, which is called the flue gas chemical recuperative cycle. This paper provides a meaningful review of the latest advancements in the flue gas chemical recuperative cycle system, focusing on its application in diverse gasification systems for organic matters such as methane, sludge, etc. Additionally, this paper reviews methods for the integration of flue gas gasification into energy conversion and utilization systems under the application scenarios of gas turbine flue gas, air combustion flue gas, and oxy-fuel combustion flue gas. Subsequently, in order to improve the conversion efficiency of the chemical recuperative cycle, the applications of emerging gasification technologies in the field of the flue gas recuperative cycle, such as microwave gasification, plasma gasification, etc., are briefly summarized, offering an in-depth analysis of the mechanisms by which new methods enhance the process. Finally, the prospects and challenges of the field are discussed, and a comprehensive outlook is provided to guide future research.